Significance of assessment experiences during initial teacher training in physical education - Wagner dos Santos; Francine de Lima Maximiano; Juliana Martins Cassani Matos; André da Silva Mello; Omar Schneider; Amarílio Ferreira Neto (Universidade Estadual Paulista (UNESP), 2016)
Abstract This study investigates how students in the final semester of their teacher training program (licensure) at the Center of Physical Education and Sports (CEFD), Espírito Santo Federal University, Brazil, (re)interpret their assessment experiences, an integral component of their teacher training. It employs the narrative as a theoretical and methodological perspective, and it utilizes student portfolios, as well as focus groups and semi-structured individual interviews as inputs for data generation. Ten students in their eighth, or final, semester participated in this study. These were the total respondents to a "call for volunteers" among the 2014 graduating class. The results suggest that the students believe the assessment processes of their teaching practices in physical education are disjointed. They feel that the disciplines that allow them to review their own performance during teacher training are more efficient and play a stronger role in their education.